Mineral matter identification in Nallihan lignite by leaching with mineral acids - Guelen, J. (TAYLOR & FRANCIS INC, 2007)
Coals are heterogeneous, complex noncrystalline macromolecules having both organic and inorganic materials that contain some inorganic constituents. Some techniques have been applied to this fossil fuel in order to remove these undesired inorganic parts from the organic part. Chemical demineralization is one of the suitable methods for removal of inorganic elements although it is an expensive way. But by this method, many elements are leached effectively from the lignite body from the point of economic view because these inorganic parts may cause some undesired deleterious effects. In this study, the demineralization effect of some aqueous acids of 5% such as HCl, H2SO4, HNO3, and HF was studied. The effect of these mineral acids was shown by X-ray spectroscopy.
Keywords: acid; demineralization; inorganic matter; lignite; X-ray spectroscopy; REMOVAL; COALS; Energy & Fuels; Engineering; Environmental Sciences & Ecology